2003
DOI: 10.1002/eji.200323328
|View full text |Cite
|
Sign up to set email alerts
|

TNF‐α impairs peripheral tolerance towards β‐cells, and local costimulation by B7.1 enhances the effector function of diabetogenic T cells

Abstract: Maintenance of peripheral tolerance and inactivation of autoreactive T cells is based on a delicate balance between pro-inflammatory and protective cytokines that is poorly understood. We have here addressed how the local expression of the inflammatory cytokine TNF- § can impair peripheral tolerance and lead to autoreactivity. After transplantation of pancreata that are immunogenic due to g -cell expression of B7.1 and TNF- § , into thymectomized and euthymic syngeneic mice, we found that only euthymic mice re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…As expected, mice with transgenic expression of B7.1 molecule and viral glycoprotein on beta cells together with glycoprotein-specific transgenic T cells develop insulitis and diabetes while mice with a combination of only two-thirds of the above transgenes do not develop diabetes [26]. Islet B7.1 expression may directly influence the threshold for autoimmune T-cell killing through enhancement of effector function of diabetogenic T cells, namely cytotoxic T lymphocytes [27][28][29]. B:9-23 peptide induced aggressive intra islet insulitis regardless of the age of onset and destruction was restricted to beta cells.…”
Section: Discussionmentioning
confidence: 90%
“…As expected, mice with transgenic expression of B7.1 molecule and viral glycoprotein on beta cells together with glycoprotein-specific transgenic T cells develop insulitis and diabetes while mice with a combination of only two-thirds of the above transgenes do not develop diabetes [26]. Islet B7.1 expression may directly influence the threshold for autoimmune T-cell killing through enhancement of effector function of diabetogenic T cells, namely cytotoxic T lymphocytes [27][28][29]. B:9-23 peptide induced aggressive intra islet insulitis regardless of the age of onset and destruction was restricted to beta cells.…”
Section: Discussionmentioning
confidence: 90%
“…However, the role of TNF-α in Type 1 diabetes is still controversial. Previous studies in animal models for Type 1 diabetes have clearly demonstrated that TNF-α could participate in the development of diabetes, while other studies have highlighted the role of TNF-α in silencing the autoimmune process, suggesting a dual role of TNF-α in the development of the disease based on the timing of TNF-α expression [47,48,49,50,51,52,53].…”
Section: Discussionmentioning
confidence: 99%
“…8 Indeed, TNF-␣, like IL-6, promotes T cell proliferation 9 and also impairs peripheral tolerance of islets. 10 It is likely that there are redundant pathways between inflammatory cytokines in immune regulation, 11 but it is not clear whether IL-6 and TNF-␣ cooperate in preventing transplant tolerance.…”
mentioning
confidence: 99%